Relationship Between Strength of Hip Muscles and Performance of Close Kinetic Chain Dynamic Lower Extremity Stability Test - Hyeon-ju Lee; Ui-jae Hwang; Sung-hoon Jung; Sun-hee Ahn; Oh-yun Kwon (Korean Research Society of Physical Therapy, 2020)
Background: The hip muscle plays various roles. Several types of functional performance tests are used for the assessment of patients with various lower extremity injuries. Hip muscle functions are important to test the performance of maintaining the spine, pelvic, and leg during bridging exercise. We designed a novel functional performance test tool, which we named close kinetic chain dynamic lower extremity stability (CKCLE) test to assess hip muscle functions. Objects: The purpose of this study was to determine the relationship between CKCLE test and hip extensor, external rotator, and abductor strengths. Methods: Twenty-two subjects were recruited in the present study (13 males and 9 females). The hip extensor, external rotator, and abductor muscle strengths were measured using a Smart KEMA strength sensor. When the examiner said "Go", the subject performed the CKCLE test by moving one leg from the floor and touching the opposite knee and then return to the floor while maintaining the bridging position. The subjects attempted as many "touches" as possible in the allotted time (20 seconds) during the maximal tests. The correlation between the hip muscle (extensor, external rotator, and abductor) strength of the supporting leg and the number of CKCLE tests performed in 20 seconds was determined using the Pearson correlation. Results: Hip extensor (r = 0.626, p < 0.05), hip external rotator (r = 0.616, p < 0.05), and hip abductor muscle strengths (r = 0.475, p < 0.05) positively correlated with the number of CKCLE tests performed. Conclusion: We designed a CKCLE test and found that performance in the test correlated with hip extensor, external rotator, and abductor muscle strengths. The result suggests that the CKCLE test can be applied as a performance test to assess the functions of the hip extensor, external rotator, and hip abductor muscles.